Stability by balanced growth: Expertise on the reform of the Stability and Growth Pact for the Group of the Progressive Alliance of Socialists & Democrats in the European Parliament - Torsten Niechoj (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
In this expertise for the European Parliament different proposals for the reform of the European Stability and Growth Pact are evaluated. The focus of the reformed pact is still on fiscal restraint, institutionalised by the 3% of GDP deficit criterion and the strengthened 60% debt-to-GDP criterion. The forthcoming pact, reformed along these lines, cannot cope with the economic challenges that led to the economic and the euro crises of the last two years. The inclusion of a framework for tackling macroeconomic imbalances could be an important step in broadening this narrow and inadequate focus. In the current form, however, a latent conflict between the excessive deficit procedure (EDP) and the new excessive imbalance procedure (EIP) exists. – – In dieser Expertise für das Europaparlament werden mehrere Vorschläge zur Reform des europäischen Stabilitäts- und Wachstumspakts miteinander verglichen und verortet. Der Fokus des reformierten Pakts ist immer noch auf fiskalische Zurückhaltung - institutionalisiert über das 3%-Defizitkriterium und das verschärfte 60%-Schuldenstandskriterium - gerichtet. Der kommende Pakt, wenn er wie geplant reformiert werden sollte, kann den ökonomischen Herausforderungen, die zu den Wirtschafts- und Eurokrisen der letzten zwei Jahre geführt haben, nicht entsprechen. Die Hereinnahme eines Verfahrens zum Umgang mit makroökonomischen Ungleichgewichten könnte ein wichtiger Schritt dahin sein, diesen engen und inadäquaten Fokus zu erweitern. In der bislang vorliegenden Form existiert jedoch ein latenter Konflikt zwischen dem Verfahren zur Behandlung exzessiver Defizite (EDP) und dem neuen Verfahren zur Behandlung exzessiver Ungleichgewichte (EIP).
urn:nbn:de:101:1-201202285353
Keywords: 330